The Shadow of Totalitarianism : Action, Judgment, and Evil in Politics. - Burdman, Javier (State University of New York Press, 2022)
Examines the relationship of evil, action, and judgment in the work of Immanuel Kant, Hannah Arendt, and Jean-François Lyotard.